PERANANAN GENDER, KETERAMPILAN KERJA DAN PERPUTARAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PABRIK TEPUNG TAPIOKA - Nurudin, Zainal Arifin; Rapini, Titi; Abrianto, Tegoeh Hari (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This research was conducted to determine the effect of Gender Roles, Work Skills, and Employee Turnover on Employee Performance at Ponorogo Tapioca Flour Factory. Determination of the sample used is a number of 100 employees or by taking 77% of the population of the number of employees at the Ponorogo Tapioca Flour Factory. Collecting data in this study by distributing questionnaires to all respondents. The analytical method in this study uses multiple linear regression analysis. The results of this study indicate that: (1) Gender roles do not significantly influence employee performance, (2) There is a positive influence of work skills (skills) on employee performance, (3) There is a negative effect on employee turnover (turnover intention) on employee performance, (4) There is a simultaneous influence of gender roles, work skills and employee turnover on employee performance